Crucial Words : Conditions for Contemporary Architecture - Wærn, Rasmus; Wingårdh, Gert (Birkhäuser, 2012)
Gert Wingårdh and Rasmus Wærn, Sweden’s most active architect and its best-known architecture critic, made a selection of approximately fifty terms and concepts, including Branding, Collaborators, Corporate, Desire, Future, Everyday, Ornament, and Wheelchair. The result is a very special dictionary with humorous illustrations and original articles.